Tei Index Is the Best Echocardiographic Parameter for Assessing Right Ventricle Function in Patients With Unrepaired Congenital Heart Diseases With Outflow Tract Obstruction - Márquez-González, Horacio; Vargas, Mario H.; Yáñez-Gutiérrez, Lucelli; Almeida-Gutiérrez, Eduardo; Garduño-Espinosa, Juan (Frontiers in Pediatrics, 2018)
Objective: Magnetic resonance imaging (MRI) and cardiac catheterization are diagnostic tools for right ventricle dysfunction (RVD), but those are expensive and often unavailable techniques. Thus, our objective was to identify clinical and/or echocardiographic variables capable of predicting a catheterization-based diagnosis of RVD. Design: This was cross-sectional, diagnostic test accuracy study, considering the catheterization-based diagnosis of RVD as the gold standard. Patients: Pediatric patients with non-repaired CHD with overload pressure were evaluated. Clinical variables (edema and functional class), transthoracic echocardiography (right heart dimensions, systolic and diastolic function, Doppler velocities), and cardiac catheterization (pressures and right ventricle systolic work measurements) were obtained during the same hospitalization. Results: We included 253 patients with tetralogy of Fallot (39.9%), pulmonary atresia with ventricular septal defect (33.9%), type C Ebstein’s anomaly (15.8%), or pulmonary stenosis (10.4%). Among clinical (vascular congestion, functional class derangement) and echocardiographic (indexed right ventricle diameter, fractional area change, tricuspid annular plane systolic excursion, S’ wave, Tei index) variables, the Tei index (defined as the ratio of isovolumetric contraction time to ejection time) was the sole variable that exhibited high diagnostic capability, with 98.5% sensitivity, 97.4% specificity, 97.8% positive predictive value, and 98.3% negative predictive value, with 98.0% overall performance. Multivariate logistic regression confirmed that Tei index alone predicted the catheterization-based diagnosis of RVD. Conclusions: Tei index is the best parameter that can be employed for the non-invasive identification of RVD in patients with CHD.